The Cultivation of Melon on Swamp Floating Bed in Central Kalimantan, Indonesia - Hastin Ernawati Nur Chusnul Chotimah; Gusti Irya Ichriani; Wahyu Widyawati; Moh Anwar; Exwan Prasetyo; Ardianor Ardianor (Journal of Wetlands Environmental Management, 2020)
Cultivating of melon particularly in Central Kalimantan has been widely undertaken by farmers, however, the yields have not been able to meet the melon needs of Central Kalimantan's community. One of the breakthroughs in overcoming the problem is by growing melons on swamp floating beds, namely ambul technology. Ambul is growing media from decomposed floating aquatic plants, constructed with bamboo or wooden as a frame, that is let floating on waters. The ambul based on the consideration that the community lacks access to land for most of the year, which reduces opportunities for growing crops. The research design used was Split Plot Design with three kinds of aquatic plants as the main factor namely Eichornia crassipes, Salvinia molesta, Eleocharis palustris, and two melon varieties as subplot factors specifically Action 434 and Amanta. The results showed that the Amanta variety grown on S. molesta media produced the highest value of crop length on 1, 2, 3 weeks after planting (WAP). S. molesta was the best planting media for enhancing flowering by 11.43 days after planting (DAP) and weight of fruit (3.18 kg per plant. The variety of Amanta also had the highest value of root dry weight of 1.33 g per plant and fruit weight of 2.08 kg per plant.